2016
DOI: 10.1002/2015jd024704
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the mean wind and its diurnal variation between wet and dry spells of the monsoon over southeast India

Abstract: The differences in the vertical structure of mean wind and its diurnal variation from the surface to upper troposphere between wet and dry spells are studied using a unique data set consisting of surface and remote sensing (SOund Detection and Ranging and wind profilers) measurements made at Gadanki (13.5°N 79.2°E). Special emphasis was given to study the variation of low‐level jet (LLJ) and tropical easterly jet (TEJ), two most conspicuous features of the Indian summer monsoon. Largest and significant wind di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
(50 reference statements)
0
10
0
Order By: Relevance
“…The associated upper air circulation extends to the upper troposphere and even to the lower stratosphere. The altitude of jet-core, strength of wind speed, and the north-south oscillations of LLJ and tropical easterly jet stream show strong association with monsoon activity 18 .…”
Section: How Do the Changes In The Tropospheric And Lower Stratospher...mentioning
confidence: 91%
“…The associated upper air circulation extends to the upper troposphere and even to the lower stratosphere. The altitude of jet-core, strength of wind speed, and the north-south oscillations of LLJ and tropical easterly jet stream show strong association with monsoon activity 18 .…”
Section: How Do the Changes In The Tropospheric And Lower Stratospher...mentioning
confidence: 91%
“…The WGs in South India block these prevailing winds and reduce the strength of the southwesterly winds on the leeward side of the mountains. Under these conditions, it was observed that lower atmospheric winds exhibited systematic diurnal variability (Mohan & Rao, 2016;Ruchith et al, 2014) over the leeward side of the WGs (Figure 5; see Figure S3). During the afternoon and evening (1430-1730 LST), the anomalous southwesterly in southeast India showed signs of weakening.…”
Section: Diurnal Variability Of Lower Atmosphere Circulation Systemmentioning
confidence: 97%
“…Land surface effects of the Indian subcontinent, including both their dynamic and their thermodynamic roles, can be major influencing factors regarding the nocturnal moist surge toward the Gangetic Plain over the western BoB. This is because the Indian subcontinent, which is located further windward, can have substantial impact on the low‐level monsoon westerlies over and around the Indian subcontinent (Mohan & Rao, 2016; Ruchith et al., 2014). In the daytime, the mixed layer develops from the surface to 850 hPa across the Indian subcontinent (Figure 4a).…”
Section: Land Surface Effects Of the Indian Subcontinentmentioning
confidence: 99%